Social networks of independents and partisans: Are independents a moderating force?. Issue 2 (1st March 2022) - Reilly, Thom; Hedberg, E. C.
Abstract: While scholars have long recognized that social networks impact political engagement for partisans, comparatively little work has examined the role of networks for independent voters. In this article, we contribute to existing research on social networks and politics by surveying Arizona registered voters about their political persuasion, personal networks, and media consumption habits. Our findings show that independents have networks that are structurally different from partisans. Specifically, we found that both Democrat and Republican respondents were more likely to frequently talk about politics with independents than with members of the opposing party. Independents were also less likely than partisans to end a friendship over a political dispute. Taken together these findings show that independents may be frequent and reliable discussion partners for partisans and may be able to moderate political views. We find evidence for the moderating force of independents is especially apparent in the media consumption habits of Republican respondents. Related Articles: Cormack, Lindsey. 2019. "Leveraging Peer‐to‐Peer Connections to Increase Voter Participation in Local Elections." Politics & Policy 47(2): 248–66. https://doi.org/10.1111/polp.12297 . Malmberg, Fredrik G., and Henrik Serup Christensen. 2021. "Voting Women, Protesting Men: A Multilevel Analysis of Corruption, Gender, and Political Participation." Politics & Policy 49(1): 126–61. https://doi.org/10.1111/polp.12393 . Rowe, Andrew D., and David E. Pitfield. 2019. "The Challenge of Social Media Incorporation: A Case Study of HACAN Clearskies." Politics & Policy 47(4): 775–806. https://doi.org/10.1111/polp.12319 . Redes sociales de independientes y partidistas: ¿son los independientes una fuerza moderadora?: Si bien los académicos han reconocido durante mucho tiempo que las redes sociales afectan el compromiso político de los partidarios, relativamente pocos trabajos han examinado el papel de las redes para los votantes independientes. En este artículo, contribuimos a la investigación existente sobre las redes sociales y la política encuestando a los votantes registrados de Arizona sobre su persuasión política, redes personales y hábitos de consumo de medios. Nuestros hallazgos muestran que los independientes tienen redes que son estructuralmente diferentes a las de los partidarios. Específicamente, encontramos que tanto los encuestados demócratas como los republicanos tenían más probabilidades de hablar con frecuencia sobre política con independientes que con miembros del partido contrario. Los independientes también eran menos propensos que los partisanos a terminar una amistad por una disputa política. En conjunto, estos hallazgos muestran que los independientes pueden ser socios de discusión frecuentes y confiables para los partidarios y pueden moderar las opiniones políticas. Encontramos evidencia de que la fuerza moderadora de los independientes es especialmente evidente en los hábitos de consumo de medios de los encuestados republicanos. 无党派人士和党派人士的社会网络:无党派人士是调节因素吗?: 尽管学者长期以来认为社会网络影响了党派人士的政治参与，但相比较而言，鲜有研究分析了无党派选民网络发挥的作用。本文中，通过调查亚利桑那州已注册选民的政治信仰、个人网络和媒体消费习惯，我们对关于社会网络和政治的现有研究作贡献。我们的研究发现表明，无党派人士网络从结构上有别于党派人士网络。具体而言，我们发现，民主党和共和党支持者更有可能与无党派人士频繁谈论政治，而不是与对立党派人士。与党派人士相比，无党派人士也不太可能因一次政治争论而结束友谊。综合来看，这些研究发现表明，无党派人士可能是党派人士频繁且可信赖的探讨伙伴，并且可能发挥调节政治观点的作用。我们发现，无党派人士对共和党支持者的媒体消费习惯产生的调节作用尤为明显。